Aortic Pseudoaneurysm Secondary to Mediastinitis due to Esophageal Perforation (2016)
Esophageal perforation is a condition associated with high morbidity and mortality rates; it requires early diagnosis and treatment. The most common complication of esophageal rupture is mediastinitis. There are several case reports in the literature of mediastinitis secondary to esophageal perforation and development of aortic pseudoaneurysm as a complication. We report the case of a patient with an 8-day history of esophageal perforation due to foreign body (fishbone) with mediastinitis and aortic pseudoaneurysm. The diagnosis was made using Computed Tomography (CT) with intravenous and oral water-soluble contrast material. An esophagogastroduodenoscopy did not detect the perforation.